Traumatic Diaphragmatic Hernia: Diagnosis and Surgical Treatment in a Five-Month-Old Pup - Kumar, Amit; Pal Singh, Inder; Kumari, Ansu; Bhardwaz, Anavil; Saini, Gitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The diaphragm serves as a muscular partition between  thoracic and abdominal cavities that extends across the  base of the thorax. The diaphragm plays a vital role during  inspiration as its contraction causes the lungs to expand  and fill with air. A diaphragmatic hernia (DH) is a condition  in which rupture of the diaphragm allows abdominal  organs to migrate into the pleural cavity. In companion  animals, blunt trauma to the abdomen due to motor vehicle  accidents is the common cause of traumatic DH (Hoddinott,  2013). Several other theories include an abrupt upsurge in  the intraabdominal pressure following a powerful blow  and failure of the glottis to remain closed, allowing the  stabilizing effect of the air-filled lungs to be lost acutely  (Hoddinott, 2013) or establishment of an acute and severe  pressure gradient between the pleural and peritoneal cavities  (Boudrieau, 1993) results in DH. The actual rupture or tear(s)  occurs in the diaphragm which is least protected by the  viscera at the time of injury.
Keywords: diaphragmatic hernia; displacement; organs; Surgical repair; respiratory distress